Teori-teori belajar bermunculan Teori Belajar Muncul Bersamaan Dengan Teori Belajar Kognitif - Amjad Aiwan; Martin Kustati; Nana Sepriyanti (FKIP Universitas Palangka Raya, 2023)
This research is to reveal the conception of learning in a psychological and Islamic perspective, learning is a process activity and is a very fundamental element in every type and level of education organizing activity. This means that the success or failure of achieving educational goals is very dependent on the learning process experienced by students, both when they are at school or in their own home or family environment. Learning theory is a pragmatic and eclectic theory. A theory with this nature is almost certainly never extreme. There is no learning theory that pays extreme attention to students only, teachers only, curriculum only, and so on. This research approach is through qualitative methods using library data without statistical data as in the quantitative method, so that its activities are often referred to as library research. In general, the results of this study prove that the cognitive view sees learning as something active. They take the initiative to find experience to learn, seek information to solve problems, rearrange and organize what already exists, whereas in an Islamic perspective, learning is an obligation for every Muslim in order to acquire knowledge and knowledge so that the level of his life increases. This is stated in the Qur'an surah al-Mujadilah verse 11 Allah will exalt those who believe among you and those who are given knowledge of several degrees. Science in this case is of course in the form of knowledge that is relevant to the demands of the times and is beneficial to human life.